Local innovation processes in Agroenergy directed at the mitigation and adaptation to climate change in Cuba - Su?rez, Jes?s; Mart?n, G.; Cepero, L.; Blanco, D.; Sotolongo, J.; Savran, Valentina; del R?o, E.; Rivero, J. L. (Cuban Journal of Agricultural Science, 2014)
Since 2009 the International Project BIOMAS-CUBA is being executed. This is focused on biomass use as renewable energy source, on contributing to improve living conditions and attaining the coexistence between mitigation and adaptation to climate change, feeding security and energetic sustainability in rural areas. BIOMAS-CUBA covers the production and utilization of biodiesel and biogas, biomass gasification and the production of bioproducts. The project is directed at the integrated production of foods and energy in the context of agroenergetic farms of agro-ecological basis, with the purpose of participating in local development. It promotes a local agricultural innovation model, with large involvement of producers and impact studies. Its phase 1 was executed in 87 scenarios of five Cuban provinces making possible the sowing of 109 ha of Jatropha curcas L. associated to cultures, the installation of a plant of biodiesel production (105 600 liters/year) and two biomass gasifiers for generating electricity, the construction of 69 biodigestors and the installation of 52 plants for the production of the IHplus bioproduct of wide spectrum of agricultural use ?in nine provinces-, with 3.4 benefit/cost, included the investment. If phase 1 was centered on the promotion of agroenergetic farms, the II (2012-2015) is directed at the formulation and implementation of local strategies of integrated production of foods and energy in six municipalities, accompanying the governments and other actors, as well as to attain greater incidence in national, regional and local policies, associated with food security, renewable energies and environment. Key words: agroenergy, climate change, food security, energy